Photo-assisted reductive cleavage and catalytic hydrolysis-mediated persulfate activation by mixed redox-couple-involved CuFeS2 for efficient trichloroethylene oxidation in groundwater. (15th August 2022) - Huang, Junyi; Zhou, Yuanhao; Deng, Shimao; Shangguan, Yangzi; Wang, Ranhao; Ge, Qiuyue; Feng, Xuezhen; Yang, Zhigang; Ji, Yongfei; Fan, Ting; Chen, Baiyang; Li, Boqiang; et al.
Highlights: CuFeS2 exhibits excellent reactivity for PS activation towards TCE degradation. Both SO4 − and OH radicals were involved in PS-CuFeS2 reaction system. Cu(I) acted as electron donors and Fe(III) as catalytic centers during PS activation. PS catalytic hydrolysis-mediated H2 O2 generation process dominated OH production. The possible TCE degradation pathways in PS-CuFeS2 system were proposed. Abstract: Persulfate (PS, S2 O8 2− ) activation through transition metal sulfides (TMS) has gained increasing attention since it can decompose a wide variety of refractory halogenated organic compounds in groundwater and wastewater. However, the processes of PS activation by TMS and particularly the formation of OH radical under anoxic and acidic conditions (pH ∼2.8) remain elusive. Herein, by employing mixed redox-couple-involved chalcopyrite (CuFeS2 ) (150 mg/L) nanoparticles for PS (3.0 mM) activation, 96% of trichloroethylene was degraded within 120 min at pH 6.8 under visible light irradiation. The combination of experimental studies and theoretical calculations suggested that the Cu(I)/Fe(III) mixed redox-couple in CuFeS2 plays a crucial role to activate PS. Cu(I) acted as an electron donor to transfer electron to Fe(III), then Fe(III) served as an electron transfer bridge as well as a catalytic center to further donate this received electron to the O–O bond of PS, thus yielding SO4 − for trichloroethylene oxidation. Moreover, for the first time, OH radicals were found to form from the catalytic hydrolysis of PS onto CuFeS2 surface, where S2 O8 2− anion was hydrolyzed to yield H2 O2 and these ensuing H2 O2 were further transformed into OH radicals via photoelectron-assisted O–O bond cleavage step. Our findings offer valuable insights for understanding the mechanisms of PS activation by redox-couple- involved TMS, which could promote the design of effective activators toward PS decomposition for environmental remediation. Graphical abstract: Image, graphical abstract